GERVIT - A tool for sports data vizualization employing Google Earth - Eskofier, B.; Melzer, D. (International Journal of Computer Science in Sport, 2009)
We developed a software tool for runners and other sportsmen that is capable of visualizing recorded Global Position System (GPS) data of sports activity. If available, heart rate (HR) as well as other meta data can be visualized along with the position. The goal of the work was to create public domain software under the general public license (GPL) for post-training-analysis of running sessions and the possibility to exchange the visualized result with others via the Internet. The software and its sources are available for download. The tool was realized using Google Earth and its Keyhole Markup Language (KML), which allows to visualize the data directly in Google Earth and to pass visualized data to others. Given the input data, our software creates a KML file. Besides the running path it is also possible to visualize speed and heart rate as well as other information such as elapsed time, average speed, average heart rate, running distance and altitude. Data from different sources can be automatically registered in order to improve visualization.